5′-UMP inhibited muscle atrophy due to detraining: a randomized, double-blinded, placebo-controlled, parallel-group comparative study - Inoue, Mika; Kubota, Atsushi; Takazawa, Yuji; Nakagawara, Kosuke; Ishige, Kazuya; Suzuki, Yoshio (Frontiers in Sports and Active Living, 2024)
Purpose A short period of disuse of 1–2 weeks due to factors such as illness or injury can lead to muscle atrophy, affecting both athletic performance and health. Recent research has shown that uridine 5′-monophosphate (5′-UMP) can counteract disuse-induced muscle atrophy by increasing PGC-1α expression and inhibiting atrogin-1 expression. However, the effect of 5′-UMP on disuse muscle atrophy in humans remains unknown. Therefore, the aimed of this study was to explore the effects of 5′-UMP supplementation during detraining on short-term disuse muscle atrophy in healthy men. Methods Following a 6-week resistance training program on upper arm, healthy men were randomized to either a UMP group (n = 11) or a placebo group (n = 10), taking their respective supplements during the 2-week detraining period. Muscle thickness, an indicator of muscle hypertrophy and atrophy, was measured at 3 positions (MT50, MT60, and MT70) at baseline, 1 week, and 2 weeks after detraining. Results Both groups showed a significant decrease in muscle thickness at MT70. The relative decrease was greater in the placebo group (2.4 ± 2.8%) than in the UMP group (0.0 ± 2.0%), significantly (p = 0.034) at 1 week. However, no significant difference was observed at MT50 and MT60. Conclusion After the hypertrophy, 5′-UMP may prevent muscle atrophy due to the detraining within the first week.